Shipwrecks and graves: Their treatment as intangible heritage - Perez-Alvaro, Elena (International Journal of Intangible Heritage, 2023)
The treatment and management of human remains in land archaeology has been a debated topic. However, in the field of underwater cultural heritage, the references are almost non-existent. The importance of the topic has already been recognised, since some nations have established legal frameworks to protect those human remains. In addition, the term is included in the definition of ‘underwater cultural heritage’ under the 2001 UNESCO Convention on the Protection of the Underwater Cultural Heritage (UNESCO 2001). However, the ethical dilemmas around the topic have not been discussed, and protocols for the management of shipwrecks with or without human remains have not been established. This article discusses the management of human remains as part of an underwater cultural heritage site and the ethical issues that this complicated heritage presents at an international level. In this regard, it looks both at those shipwrecks that still preserve human remains and those where the remains have disappeared but were once there. It also introduces three concepts, applied for the first time to human remains, based on a variety of cultural attitudes: absent, invisible and intangible heritage.
Keywords: underwater cultural heritage; shipwrecks; watery graves; respect; sacred places; WOS